Writing superiority in cued recall - Fueller, Carina; Loescher, Jens; Indefrey, Peter (Frontiers in Psychology, 2013)
In list learning paradigms with free recall, written recall has been found to be less susceptible to intrusions of related concepts than spoken recall when the list items had been visually presented. This effect has been ascribed to the use of stored orthographic representations from the study phase during written recall (Kellogg, 2001). In other memory retrieval paradigms, either better recall for modality-congruent items or an input-independent writing superiority effect have been found (Grabowski, 2005). In a series of four experiments using a paired associate (PA) learning paradigm we tested (a) whether output modality effects on verbal recall can be replicated in a paradigm that does not involve the rejection of semantically related intrusion words, (b) whether a possible superiority for written recall was due to a slower response onset for writing as compared to speaking in immediate recall, and (c) whether the performance in PA word recall was correlated with performance in an additional episodic memory task. We found better written recall in the first half of the recall phase, irrespective of the modality in which the material was presented upon encoding. An explanation based on longer response latencies for writing and hence more time for retrieval could be ruled out by showing that the effect persisted in delayed response versions of the task. Although there was some evidence that stored additional episodic information may contribute to the successful retrieval of associate words, this evidence was only found in the immediate response experiments and hence is most likely independent from the observed output modality effect. In sum, our results from a PA learning paradigm suggest that superior performance for written versus spoken recall cannot be (solely) explained in terms of additional access to stored orthographic representations from the encoding phase. Our findings rather suggest a general writing-superiority effect at the time of memory retrieval.